Estimating the Eggs Numbers of Tent Caterpillar Malacosoma neustria (Linnaeus) on Apple and Oak Trees in Al-Jabal Al-Akhdar-Libya - Mustfa, Kamla A. A; Amin, Adil H.; El-Ghariani, I. (Al-Mukhtar Journal of Sciences, 2002)
Different experiments were conducted in Al-Jabal Al-Akhdar regions located North-East of Libya during the seasons 96/97, to estimating the number of eggs in each single egg-mass of tent caterpillar Malacosoma neustria (Linnaeus) on two kinds of host trees, apple Malus domestica and oak Quercus coccifera. The length, diameter and lateral area of egg-mass, also the diameters of branch covered by the egg-mass were investigated. The results revealed that the lateral area of egg-mass was the best one to estimate the egg number within single egg-mass on the two hosts. Also the data showed that the fecundity of the insect was higher on the oak than on the apple.